Thermal properties of alkali-treated sugar palm fibre reinforced high impact polystyrene composites - Bachtiar, Dandi; Salit, Mohd Sapuan; Zainudin, Edi Syams; Abdan, Khalina; Mohd Dahlan, Khairul Zaman (Universiti Putra Malaysia Press, 2013)
Thermal characterization of sugar palm fibre (SPF), reinforced high impact polystyrene (HIPS) composites, was studied by means of thermogravimetric analysis. The effects of alkaline treatment and compatibilizing agent on the thermal stability of the composites were evaluated. Alkaline treatment was carried out by soaking the fibres in 4 and 6% of NaOH solution, while treatment with compatibilizing agent was employed by adding 2 and 3% maleic anhydride-graft-polystyrene (MA-g-PS) to the composites. Both the treatments were aimed to improve the mechanical performance of the composites. From the study, the thermal stability of the treated composites was found to be higher than that of untreated composites. It is shown that the incorporation of sugar palm fibre influences the degree of thermal stability of the composites. The treatments on composites also contributed to shifting the peak temperature of degradation of the composites. In other words, there are strong chemical reactions between the components of the treated composites. The thermal stability of the composites, with alkaline treatment and compatibilizing agent, was found to be better as compared to those of the untreated composites.